Association between hemoglobin glycation index and cardiometabolic risk factors in Korean pediatric nondiabetic population - Bora Lee; You Jung Heo; Young Ah Lee; Jieun Lee; Jae Hyun Kim; Seong Yong Lee; Choong Ho Shin; Sei Won Yang (Korean Society of Pediatric Endocrinology, 2018)
Purpose The hemoglobin glycation index (HGI) represents the degree of nonenzymatic glycation and has been positively associated with cardiometabolic risk factors (CMRFs) and cardiovascular disease in adults. This study aimed to investigate the association between HGI, components of metabolic syndrome (MS), and alanine aminotransferase (ALT) in a pediatric nondiabetic population. Methods Data from 3,885 subjects aged 10-18 years from the Korea National Health and Nutrition Examination Survey (2011-2016) were included. HGI was defined as subtraction of predicted glycated hemoglobin (HbA1c) from measured HbA1c. Participants were divided into 3 groups according to HGI tertile. Components of MS (abdominal obesity, fasting glucose, triglycerides, high-density lipoprotein cholesterol, and blood pressure), and proportion of MS, CMRF clustering (≥2 of MS components), and elevated ALT were compared among the groups. Results Body mass index (BMI) z-score, obesity, total cholesterol, ALT, abdominal obesity, elevated triglycerides, and CMRF clustering showed increasing HGI trends from lower-to-higher tertiles. Multiple logistic regression analysis showed the upper HGI tertile was associated with elevated triglycerides (odds ratio, 1.65; 95% confidence interval, 1.18-2.30). Multiple linear regression analysis showed HGI level was significantly associated with BMI z-score, HbA1c, triglycerides, and ALT. When stratified by sex, age group, and BMI category, overweight/obese subjects showed linear HGI trends for presence of CMRF clustering and ALT elevation. Conclusions HGI was associated with CMRFs in a Korean pediatric population. High HGI might be an independent risk factor for CMRF clustering and ALT elevation in overweight/obese youth. Further studies are required to establish the clinical relevance of HGI for cardiometabolic health in youth.